Sebaceous neoplasms in siriraj hospital, Mahidol university: A 9-year-retrospective study - Jane Manonukul (2018)
Background: Sebaceous neoplasms are adnexal neoplasms that contain a varying number of sebocytes, i.e. large cells with lipid-laden vacuolated cytoplasm, soap-bubble in appearance, and crenate nuclei. They are uncommon compared to other adnexal neoplasms. Various sebaceous neoplasms with complex histopathologic features and varying degree of sebaceous cells differentiation have been described in the literature. Objectives: To study the prevalence of ebaceous neoplasms, i.e. nevus sebaceus, sebaceous hyperplasia, sebaceous adenoma, sebaceoma, sebaceous pithelioma, superficial epithelioma with sebaceous differentiation, and sebaceous carcinoma diagnosed in the Department of Pathology, Siriraj Hospital, Mahidol University during the 9-year-period between 1997 and 2005. To study the prevalence of tumor transformation that occurs in nevus sebaceus. Material and Method: A retrospective study of all sebaceous neoplasms including Nevus sebaceous, sebaceous hyperplasia, sebaceous adenoma, sebaceoma, sebaceous epithelioma, superficial epithelioma with sebaceous differentiation, sebaceous carcinoma, and all neoplasms containing the term "sebaceous" was performed. All slides were re-analyzed and re-diagnosed, without knowledge of the previous diagnosis or any clinical data, according to the criteria described in the standard textbooks of dermatopathology by Elder, McKee. Comparison between the previous diagnoses and the reviewed diagnoses was performed to assess the initial accuracy of all sebaceous neoplasms diagnosed. Small-sized biopsies or biopsies that possess incomplete sebaceous differentiation, in which the sebocytes were few and subtle, sometimes are difficult to diagnose. In these instances, the clinical correlation was needed for positive diagnosis. Afterwards, these reviewed diagnoses were recorded and classified according to the patient's age, gender, and localization. Results: Two hundred seven sebaceous neoplasms (2.34%) from the 8819 skin biopsies that were taken in the Department of Pathology, Siriraj Hospital during the 9-year-period, were included. After exclusion of some authentically non-sebaceous neoplasms, 182 sebaceous neoplasms were found. Nevus sebaceus (n = 85, 46.7%) and sebaceous hyperplasia (n = 64, 35.1%) were the two most common benign lesions. The others were sebaceoma (n = 3, 1.6%), sebaceous adenoma (n = 2, 1.1%), sebaceous epithelioma (n = 1. 0.5%), sebaceous carcinoma (n = 26, 14.3%), and one unclassified sebaceous lesion that could not be considered a neoplasm. Tumor degeneration was found in 14 nevus sebaceus in which 21 neoplasms existed, namely, trichilemmoma (wart)-like lesion (n = 4), primitive follicular induction (n = 7), syringocystadenoma papilliferum (n = 3), trichoblastoma (n = 3), and one of each of trichoepithelioma, sebaceous adenoma, tumor of follicular infundiculum, and mucoepidermoid carcinoma. Conclusion: Twenty-six sebaceous carcinomas out of 182 sebaceous neoplasms, occurring mostly on the patients' eyelids, were found. The most common sebaceous neoplasm was nevus sebaceus (n = 85); the prophylactic excision of this lesion was recommended as tumor degeneration was frequent (14 out of 85 cases). Epithelial membrane antigen (EMA) usually decorated both normal and abnormal sebocytes. It was very helpful in the detection of sebocytes in basaloid cells in sebaceous neoplasms and among lymphoid cells within metastasized lymph nodes and a discriminant between sebaceous and onsebaceousneoplasms.